Proposed insurance and reserve management scheme for Singapore electricity market - Xia, Linmin (2008)
The objective of the research is to improve the market design in the Singapore Electricity Market. There are three aspects that this thesis tries to improve, i.e. loss of load compensation, reserve requirement criterion and reserve market settlement. Three new designs are proposed for incorporation in the Singapore Electricity Market respectively. They are the insurance scheme on the generation side, probabilistic reserve with demand side participation and probabilistic zero-sum settlement.